Juridical Analysis of Player Abuse of Referees in Soccer Matches - Haris, Haris; Ilham Arif Budiman (Universitas Muhammadiyah Malang, 2023)
In football matches, there are often beatings (mistreatment) committed by players against referees. This study aims to analyze the mistreatment of players against referees in football matches, which can be categorized as criminal acts, and analyze actions that can be taken by the police and PSSI against mistreatment or fights between players in football matches. This research uses the sociological-judical approach. The results showed that the actions of the players who mistreated the referee met the elements of the criminal act of persecution as stipulated in Article 351, Paragraph 1, of the Criminal Code. Second, the actions of the police in the case are: a. conduct an investigation by summoning the two players who clashed on the field; b. dismiss the case on the grounds that it is submitted to the PSSI's internal decision; while the PSSI in this case only imposed sanctions with a ban from competing for the next two matches and a fine. Abstrak Dalam pertandingan sepak bola sering kali terjadi pemukulan (penganiayaan yang dilakukan oleh pemain terhadap wasit). Penelitian ini bertujuan untuk menganalisis perbuatan penganiayaan pemain terhadap wasit dalam pertandingan sepak bola tersebut dapat dikategorikan sebagai tindak pidana, dan menganalisis tindakan yang dapat dilakukan oleh pihak kepolisian dan PSSI terhadap penganiayaan atau perkelahian antar pemain dalam pertandingan sepak bola. Penelitian ini menggunakan metode pendekatan yuridis sosiologis. Hasil penelitian menunjukan bahwa perbuatan para pemain yang melakukan penganiayaan kepada wasit memenuhi unsur tindak pidana penganiayaan sebagaimana diatur dalam pasal 351 ayat (1) KUHP. Kedua, bahwa tindakan pihak kepolisian dalam kasus tersebut adalah: a. Melakukan penyidikan dengan memanggil kedua pemain yang bentrok di lapangan; b. Menghentikan perkara tersebut, dengan alasan diserahkan kepada putusan internal PSSI; sedangkan PSSI dalam kasus tersebut, hanya menjatuhkan sanksi beruapa larangan bertanding selama 2 pertandingan berikutnya, ditambah denda.